Od „wjeżdżania w bramy” do „otwierania (się) bramy”. Przykład animacji kultury upełnomocniających głos dziecka w procesie rewitalizacji miejskiej - Anita Gulczyńska; Monika Wiśniewska-Kin (Problemy Wczesnej Edukacji)
The subject of our study is the positionality of children in the process of urban revitalization. We understand the city as a learning space. From our point of view changes introduced into that space are always interventions into children’s learning processes. In the article we present an empirically based reconstruction of practices of community cultural animations that aim at empowering children’s voice in the processes of revitalization. Konrad Dworakowski’s and Pinokio Theatre’s community cultural animations, realised from 2014 to 2019 in Łódź, offer interesting examples of such practices. Even though we build or argument on the basis of observations collected in Łódź, it can be reliably reflected in discussions on educational issues in urban changes in other post-industrial cities.